2018
DOI: 10.3857/roj.2018.00073
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and feasibility of concurrent chemoradiotherapy using simultaneous integrated boost-intensity modulated radiotherapy with and without induction chemotherapy for locally advanced pancreatic cancer

Abstract: PurposeTo evaluate the effectiveness and feasibility of chemoradiotherapy (CRT) using simultaneous integrated boost-intensity modulated radiotherapy (SIB-IMRT) in locally advanced pancreatic cancer (LAPC) patients.Materials and MethodsBetween January 2011 and May 2015, 47 LAPC patients received CRT using SIB-IMRT. Prior to SIB-IMRT, 37 patients (78.7%) received induction chemotherapy (IC-CRT group) and remaining 10 patients (21.3%) did not received induction chemotherapy (CRT group). During SIB-IMRT, all patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…1 ). The dose-volume constraints for the OARs were described previously 15 , 16 , 27 . In brief, the maximum dose to the spinal cord was less than 27 GyE; the absolute volumes of the stomach receiving ≥ 37 GyE and bowel receiving ≥ 35 GyE were less than 2 cm 3 ; and the relative volumes of the liver receiving ≥ 27 GyE and kidney receiving ≥ 18 GyE were less than 60% and 35%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…1 ). The dose-volume constraints for the OARs were described previously 15 , 16 , 27 . In brief, the maximum dose to the spinal cord was less than 27 GyE; the absolute volumes of the stomach receiving ≥ 37 GyE and bowel receiving ≥ 35 GyE were less than 2 cm 3 ; and the relative volumes of the liver receiving ≥ 27 GyE and kidney receiving ≥ 18 GyE were less than 60% and 35%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Finally in locally advanced it has been observed that there is a higher effectiveness when chemoradiotherapy is applied simultaneously for locally advanced pancreatic cancer 70. Regarding borderline resectable patients then it has been observed in a Phase II trial that preoperative FOLFIRINOX followed by individualized chemoradiotherapy in borderline resectable pancreatic cancer results in high rates of R0 resection and prolonged median PFS and median OS, supporting ongoing phase 3 trials 71.…”
Section: Molecular Pathwaysmentioning
confidence: 87%
“…Several authors have investigated the feasibility of the SIB technique for the treatment of primary and metastatic brain lesions 23,24,26,28,[33][34][35][36][37][38] . Rodrigues et al 24 delivered 60 Gy in 10 fractions to 1-3 brain metastases synchronously with 30 Gy whole brain irradiation (WBRT) using HT.…”
Section: Discussionmentioning
confidence: 99%